Comparative study of switchable filters and a new technique of bandstop to bandpass filter using lossy resonators - Zahari, M.K. (Asian Research Publishing Network, 2016)
In this paper, the comparative studies of switchable bandstop to bandpass (or bandpass to bandstop) are presented. It shows that by using microstrip technology, high-Q bandstop to bandpass responses is difficult to achieve. Therefore, this paper proposes a new technique of matched bandstop to bandpass filter using two lossy low-Q resonators. The proposed technique is implemented based on perfectly-matched bandstop topology which is not only produced high-Q bandstop filter, but also easy to switch from bandstop to bandpass response. The PIN diodes (as switching element) that used in this proposed technique are incorporated into the topology to exhibit either matched bandstop response or bandpass response by turning "ON" and "OFF" of the PIN diodes. The proposed technique based on simulation result was carried out. As a result, it was found that the proposed technique was able to switch the microstrip filter from matched bandstop to bandpass filter using two lossy low-Q resonators. Â© 2006-2016 Asian Research Publishing Network (ARPN).